Subaqueous soil sequence in marine waters of the Strunjan Bay - Repe, Blaž (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2023)
Soil research focuses mainly on soils on land, but the process of soil formation also takes place in shallow waters. Subaqueous soils form below the water surface, mainly on the bottom of shallow, stagnant waters such as bogs, swamps, lakes, and shoals in the sea. Three subaquatic soil profiles were investigated in the Strunjan Bay to study them in detail. The sites for the soil investigation were selected after observing the movement of seawater and thus its possible influence on subaquatic soils. All the so-ils studied are permanently and year-round under water. Therefore, all soil samples were collected under water using drainage pipes and by excavation. The samples were slowly drained in the pipes to prevent mixing of the material and to keep the horizons as intact as possible. Visual observations and standard analyses were carried out in the laboratory according to the identified horizons. During the investigation, we found that apart from water properties and movement, most soil-forming factors can be considered constant, so we investigated and presented a soil hydrosequence. According to the WRB classification, the subaqueous soils in the waters of the Strunjan Bay were divided into the reference groups Gleysols and Leptosols.
Keywords: klasifikacije prsti; pedogeografija; pedogeography; podvodne prsti; Slovenia; Slovenija; soil classifications; soil types; Strunjan; subaqueous soils; tipi prsti